Enhancement of gain using a multilayer superstrate metasurface cell array with a microstrip patch antenna - ِAli Khalid Jassim; Malik Jasim Farhan; Fadia Noori Hummadi Al-Nuaimy (Institute of Advanced Engineering and Science, 2021)
This research presents a new idea in the use of wireless communication antennas: it uses a multi-layered array of cells called a superstrate multi-layer metasurface (MTM) and is placed in front of a patch of microstrip antenna to absorb surface waves and prevent them from passing through the insulating material, which reduces the permeability of the insulator and thus improves the Antenna properties, The proposed hexagonal cell with resonators is placed on the flame resistant (FR4) substrate, with a relative permittivity of 4.3 and an area (14×14) mm2 . It was tested when the metasurface layer is 4 mm in front of the patch and the distance between the metasurface layers is 2 mm. The optimum distances were calculated by the sweep parameter, and the improved antenna gain and the input reflection coefficient were obtained together. (S11) has been improved from -31.217 to -38.338 dB and, the gain from 3.28 dB to 6.554 dB.